Politik Identitas dan Krisis Kebhinekaan: Perspektif Moral Kebangsaan Buya Syafii Maarif - Septiyadi, Nur Rahmad Teguh; Hasanah, Noor (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
Identity politics has become a phenomenon that has been widely discussed by society recently. There are various kinds of assessments given by the public to its practices, both negative and positive. Identity politics is something that cannot be separated from some politicians, because it is through identity politics that a politician defines his or her own identity. Many experts have commented on this phenomenon, one of which is Buya Syafi'I Ma'arif. He believes that identity politics is a natural thing for a politician to do as a form of personal branding. Beliay also believes that without religion politics will be blind. On the other hand, the practice of identity politics in Indonesia has its own challenges amidst a pluralistic society. Using qualitative methods, this research attempts to find data regarding identity politics in the form of literature which is then analyzed, giving rise to two implications that identity politics has the potential to bring positive and negative things to the diversity of society.